Analisa Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Aparatur Sipil Negara pada Kantor Wilayah Direktorat Jenderal Pajak Kalimantan Timur dan Utara - Kartika Aan Wibisono; Nuraisyah; Ani Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of leadership style, family support, and work environment on the job satisfaction of Civil Servants (ASN) at the Regional Office of the Directorate General of Taxes (DGT) of East and North Kalimantan. The research employs a quantitative approach, collecting data through questionnaires distributed to 143 ASNs as a full sample. Data analysis was conducted using validity tests, reliability tests, descriptive statistics, and multiple regression analysis via SPSS. The results indicate that participative leadership style, family support, and work environment significantly influence ASN job satisfaction. Collectively, these three variables explain 75.8% of the variance in ASN job satisfaction levels (Adjusted R-Square = 0.758). Participative leadership style contributes to enhancing employees' sense of involvement, family support plays a crucial role in emotional well-being, and a conducive work environment promotes comfort and work productivity. In conclusion, ASN job satisfaction at the Regional Office of the DGT of East and North Kalimantan is significantly influenced by leadership style, family support, and work environment. Therefore, improving these factors can support the organization in achieving optimal performance.